An overview of the principle of separate legal entity from Islamic perspective - Muhammad Fakhri, Siti Maryam Dania; Husin, Adryana Iwani; Aimi, Amirah Ainina; Noor Azhar, Noriznan Izzani; Mohd Padil, Hazlina (2023)
The incorporation of a company is the result of an association between a few people (shareholders) who contribute a certain sum of money with the same objective of maximising profits through a platform called “company”. Upon incorporation, there will be a separate entity of a company different from the original members who associated themselves to be the shareholders of the company. Although common law recognises the principles of separate legal entity in a company, the same is not recognised from the Islamic point of view since Islamic teaching only recognises the ‘real’ entity, a natural person contrary to common law which recognises a legally fictitious person. Research on the principle of separate legal entity from the Islamic perspective is sparse. This paper aims to explore the principle of separate legal entity from the Islamic point of view. This research found that although the principle of separate legal entity is not recognise under Islamic law, there is evidence that modern Muslim jurists have accepted the principle in Islam with careful treatment, and adherence to certain conditions to be in line with the Shariah Law. The outcome of this study adds valuable insights into legal knowledge, particularly in corporate law and Islamic Law.